A Study on Pseudomonas aeruginosa in Chicken Meat: Isolation, Molecular Characterization, and Virulence Genes Detection - Boddepalli, Srilatha; Supriya Racharla, Annie; Kiranmayi Chinnam, Bindu; Valeti, Samatha (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Foodborne diseases caused by contaminated foods pose significant economic and public health risks worldwide. This study focused on the isolation and molecular characterization of Pseudomonas aeruginosa from chicken meat and contaminated surfaces, including cutting boards, knives, and workers hands in retail chicken meat outlets. A total of 250 samples were analyzed, comprising 191 chicken meat samples, 20 cutting board swabs, 20 knife swabs, and 19 hand swabs. Conventional methods identified P. aeruginosa in 30 (12.0%) samples, of which 20 (8.0%) were confirmed via species-specific PCR. The highest occurrence was in cutting board swabs (20.0%), followed by knife swabs (10.0%) and chicken meat (7.32%), while no isolates were found in hand swabs. Virulence gene analysis revealed that P. aeruginosa harbored multiple pathogenic factors. Among 20 isolates, 12 (60.0%) carried the lasB gene, 6 (30.0%) carried exoS, 11 (55.0%) carried plcH, and none harbored algD. The lasB gene was most prevalent in cutting board swabs (75.0%), exoS was equally present in cutting board and knife swabs (50.0%), while plcH was most frequent in chicken meat (57.14%). These findings highlight the potential risk of P. aeruginosa contamination in poultry retail environments.